2017
DOI: 10.1002/qj.3197
|View full text |Cite
|
Sign up to set email alerts
|

The severe hailstorm in southwest Germany on 28 July 2013: characteristics, impacts and meteorological conditions

Abstract: At the end of July 2013, a series of severe thunderstorms associated with heavy rainfall, severe wind gusts and large hail affected parts of Germany. On 28 July 2013, two supercells formed almost simultaneously in southern Germany, from which only the more southerly cell produced hailstones up to 10 cm in diameter on a hailswath approximately 120 km long and 15–20 km wide. For the insurance industry, this event, with losses of more than EUR 1 billion, was one of the most expensive natural disasters that has ev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
38
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 62 publications
(42 citation statements)
references
References 48 publications
4
38
0
Order By: Relevance
“…This situation often implies southerly advection of moist and warm air at low levels with sensible‐heat fluxes towards the surface water accounting for the positive SST anomaly. Associated southerly flow aloft also has an increased likelihood for the advection of an elevated mixed layer (EML), known as the Spanish Plume over western France, which produces a conditionally unstable environment favourable to the development of severe convective storms (Carlson and Ludlam, ; Carlson et al ., ; Lanicci and Warner, ; Lewis and Gray, ; Kunz et al ., ). Overall, the influence of the SST anomalies is spatially extended and affects most parts of France and Spain in the case of SST − , and entire western and central Europe in the case of SST + .…”
Section: Resultsmentioning
confidence: 99%
“…This situation often implies southerly advection of moist and warm air at low levels with sensible‐heat fluxes towards the surface water accounting for the positive SST anomaly. Associated southerly flow aloft also has an increased likelihood for the advection of an elevated mixed layer (EML), known as the Spanish Plume over western France, which produces a conditionally unstable environment favourable to the development of severe convective storms (Carlson and Ludlam, ; Carlson et al ., ; Lanicci and Warner, ; Lewis and Gray, ; Kunz et al ., ). Overall, the influence of the SST anomalies is spatially extended and affects most parts of France and Spain in the case of SST − , and entire western and central Europe in the case of SST + .…”
Section: Resultsmentioning
confidence: 99%
“…This supports the statement of Piper et al (2019) that convective predisposition is decisively influenced by the state of mid-tropospheric flow steering the large-scale thermodynamic and dynamic conditions relevant for convection. Flow patterns, for example, associated with advection of warm air masses at low levels from southwesterly regions from Spain to France and central Europe in combination with an elevated mixed layer (Carlson et al, 1983;Lanicci and Warner, 1991) and a Spanish plume event (Morris, 1986;van Delden, 2001;Piper, 2017) often produce a conducive environment for the development of (severe) thunderstorms (Kunz et al, 2018;Piper et al, 2019).…”
Section: For Both Areas Approximately 22% Of the Days Betweenmentioning
confidence: 99%
“…The convection permitting model used is COSMO‐IL with a 2.5 km resolution, based on the primitive thermo‐hydrodynamic equations that describe non‐hydrostatic compressible flow in a moist atmosphere. The model uses a rotated geographical Arakawa C‐grid and generalized terrain following height coordinates with a Lorenz vertical staggering method (Steppeler et al ., ; Baldauf et al ., ; Doms et al ., ; Kunz et al ., ). Its vertical extension reaches 23.5 km (about 30 hPa) with 60 model levels in the atmosphere.…”
Section: Methodsmentioning
confidence: 99%
“…During recent years, numerous studies have been devoted to exploring the effect of the resolution of NWP models on the quality of precipitation forecasts for different synoptic conditions and geographical areas. The most remarkable feature of numerical models with a grid spacing <2–4 km is the possibility to treat deep convection explicitly instead of using a traditional convection parameterization (Noppel et al ., ; Kunz et al ., ). Many studies have shown that such models provide quantitatively better results in terms of the simulated precipitation amount, its structure and timing (e.g.…”
Section: Introductionmentioning
confidence: 99%